Effect of Antibiotics on the Colonization of Live Attenuated Salmonella Enteritidis Vaccine in Chickens - Hu, Jiangang; Che, Chuanyan; Zuo, Jiakun; Niu, Xiangpeng; Wang, Zhihao; Lian, Liyan; Jia, Yuanzheng; Zhang, Haiyang; Zhang, Tao; Yu, Fangheng; Nawaz, Saqib; Han, Xiangan (Frontiers in Veterinary Science, 2021)
Salmonellosis caused by Salmonella Enteritidis is a prevalent zoonosis that has serious consequences for human health and the poultry sector's development. Salmonella Enteritis live vaccine (Sm24/Rif12/Ssq strain) is used to prevent Salmonella Enteritidis in the world. However, in some parts of the world poultry flocks are frequently raised under intensive conditions, with significant amounts of antimicrobials used to prevent and treat disease and to promote growth. To investigate whether antibiotics use affects the colonization of orally administered Salmonella live vaccines, 240 one-day-old Specific Pathogen Free (SPF) chicks were randomly divided into 24 groups of 10 animals for this study. Different groups were treated with different antibiotics, which included ceftiofur, amoxicillin, enrofloxacin, lincomycin-spectinomycin. Each group was immunized at 2 d, 3 d, 4 d, and 5 d after withdrawal, respectively. At 5 d after immunization, the blood, liver and ceca plus content were collected for the isolation of the Salmonella live vaccine strain. The result showed that no Salmonella vaccine strain was isolated in the blood and liver of the chicks in those groups. The highest number of Salmonella vaccine strains was isolated in the cecum from chicks vaccinated 2 d after the ceftiofur withdrawal, and no Salmonella vaccine strain was isolated from the cecum in chicks immunized 3 d after the ceftiofur withdrawal. Among the chickens immunized 4 d after the withdrawal of amoxicillin, enrofloxacin and lincomycin-spectinomycin, the number of Salmonella vaccine colonization in the cecum was the highest, which was higher than that of the chickens immunized at other withdrawal intervals (2 d, 3 d, 5 d) groups, and was higher than that of the chickens without treatment (P < 0.05). This study provides a reference for the effective use of the Salmonella Enteritidis live vaccine and key antibiotics commonly utilized in the poultry industry.